Synthesis and biological evaluation of phthalimide dithiocarbamate and dithioate derivatives as anti-proliferative and anti-angiogenic agents-I - Zahran, Magdy; Agwa, Hussein; Osman, Amany; Hammad, Sherif; El-Aarag, Bishoy; Ismail, Nasser; Salem, Tarek; Gamal-Eldeen, Amira (European Journal of Chemistry, 2017)
A facile synthesis of new phthalimide dithiocarbamate and dithioate analogs 8a-j, 9a-e and 9g-j were achieved by the reaction of N-chloromethyl and N-bromoethylphthalimide with carbon disulfide (CS2) and various amines. The structures of the synthesized analogs were elucidated by spectroscopic methods, including IR, 1H NMR and 13C NMR, and ESI-HRMS techniques. The antiproliferative activity of the newly synthesized compounds was also evaluated against various human cancer cell lines. The compound 9e and 9i exhibited the highest activity against human breast adenocarcinoma MCF-7 and hepatocellular carcinoma HepG2 cells. Compound 8f showed better antiproliferative effect against colon carcinoma HCT-116 and cervical carcinoma HeLa compared to thalidomide. The binding affinity to vascular endothelial growth factor receptor (VEGFR) of some compounds was assessed in addition to molecular docking study. Compounds 9e and 9i showed high docking score values and they significantly declined the concentration of VEGFR.